OPTIMIZATION OF LIDAR SYSTEMS MEASUREMENTS FOR DETECTION OF CLEAR AIR TURBULENCE - ȘTEFĂNIE, Horațiu; BOTEZAN, Camelia; AJTAI, Nicolae; RADOVICI, Andrei; MEREUŢӐ, Alexandru; PÂRLOAGĂ, Răzvan; BELEGANTE, Livio (Studia Universitatis Babeș-Bolyai Ambientum, 2019)
In this paper we analyse the optimization of lidar systems in order to investigate Clear Air Turbulence (CAT), which is a dangerous weather phenomenon affecting especially the commercial aircrafts. It is assumed that aircrafts can cause air turbulence that can be detected by lidar, since pressure gradients could cause slight variations of the molecular depolarization values. This study will assess the capability of the lidar systems to highlight air turbulence from depolarization profiles. In order to do this, lidar measurements were performed at two sites in Romania: one in Magurele, near Bucharest and one in Cluj-Napoca. The measurements were accompanied by continuous flight path monitoring to mark the incidence events above the measuring locations.